Improving Children's Language Development Aspects through Role Playing at Mutiara Hati Kindergarten - Zainiah, Veni; Susanto, Rezi; Fitri, Yulia Rahmi (Strata Social and Humanities Studies, 2025)
This classroom action research (CAR) aimed to enhance children's language development through role-playing at Mutiara Hati Kindergarten in Solok Selatan. Language skills are crucial for early childhood communication, cognition, and socialization, yet many schools prioritize literacy and numeracy over holistic development. The study involved 10 children and one teacher across two cycles, using observation (based on Indonesian Ministry of Education benchmarks) and documentation. Results showed significant improvement: while Cycle I saw most children at "Beginning to Develop" (MB) or "Developing as Expected" (BSH), Cycle II achieved 75% in BSH or "Very Well Developed" (BSB), aligning with Vygotsky’s and Bruner’s theories on social interaction and contextual learning. The findings confirm role-playing as an effective method, with recommendations for thematic variety, teacher scaffolding, and parental involvement. Further research could integrate storytelling or multimedia for optimal outcomes.